Clot Strength is Negatively Associated With Ambulatory Function in Patients With Peripheral Artery Disease and Intermittent Claudication. (April 2015) - Mauer, Karin; Gardner, Andrew W.; Dasari, Tarun W.; Stoner, Julie A.; Blevins, Steve M.; Montgomery, Polly S.; Saucedo, Jorge F.; Exaire, J. Emilio
Peripheral artery disease (PAD) is associated with exercise impairment and greater thrombotic risk. We investigated whether clot formation and platelet aggregation assessed by thromboelastography and light-transmission aggregometry correlate with the severity of symptomatic PAD assessed by ambulatory function measures. We studied 40 symptomatic patients with PAD in whom severity of disease was assessed using ankle–brachial index, peak walking time (PWT), claudication onset time, peak oxygen uptake, daily ambulatory activity, and walking impairment questionnaire (WIQ) scores. Clot strength correlated negatively with peak oxygen uptake, PWT, WIQ distance, and stair-climbing scores. Time to clot formation did not correlate with exercise parameters. Platelet aggregation was negatively correlated with WIQ distance score and was positively correlated with PWT and peak oxygen uptake. In conclusion, clot strength and platelet aggregation correlated with objective and self-perceived ambulatory measures. Patients with PAD having more severe walking impairment may be likely to form stronger clots.